Potential Analysis and Evaluation of Drinking Water Supply Based on Independent Smart Drinking Water Platforms in Depok City - Sudirman; Heri Suprapto; Nurina Yasin (Publikasi Indonesia, 2024)
Tirta Asasta Depok has made the Independent Smart Drinking Water Platform which is prepared as a special program that is placed in public places. Currently, there are 3 (Three) Independent Smart Drinking Water Platforms installed throughout the Depok City area. The Mandiri Smart Drinking Water Platform aims to be a facility that can be enjoyed by customers in particular and the general public so that they can enjoy the processed water of the Mandiri Smart Drinking Water Platform. The installation of this machine is a form of effort by PT. Tirta Asasta Depok (Perseroda) in order to encourage the people of Depok City to be able to reduce bottled water consumption so that they can reduce the contribution of waste in the Depok City environment. People can use tumblers to buy drinking water, so that plastic bottle packaging waste can be minimized. Therefore, it is necessary to evaluate the effectiveness of the use of the Mandiri Smart Drinking Water Platform that has been installed and the potential for the installation of the Mandiri Smart Drinking Water Platform program in the future so that it becomes a consideration for the installation of the Mandiri Smart Drinking Water Platform which will be planned next. The results of the evaluation of the use of this machine still need control and regulation as well as official levies. The installation of this machine has a lot of water consumption opportunities in schools. Based on the weighting assessment that has been calculated, there are 9 (nine) agencies and schools that can be recommended (with a total value of > 15.00 points).